Actions to address food security and nutrition under climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
Delivering action on food and nutrition security in an age of global climate disruption. Read the full report back and download the issues paper: https://ccafs.cgiar.org/blog/delivering-action-food-and-nutrition-security-age-global-climate-disruption Participants report back from the Seminar on Food and Nutrition Security, Agriculture and Climate Change which took place on 7 December 2014 in Lima, Peru. Featuring experts from CARE international, CTA, CGIAR, Government of Peru, Farmers organisations, and many more.